Wnioskowanie na podstawie wyników analizy SWOT - Matyjas, Zbigniew (Interpreting the outcomes of SWOT analysis, 2006)
The main topic of the paper was the problem of interpreting SWOT analysis outcomes. After describing methods of conducting the analysis, the author focuses on the problem of SWOT analysis interpretation in terms of nine-field matrix of strategic moves of a company.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1137, s. 114-120